Association of the epithelial-to-mesenchymal transition phenotype with responsiveness to the p21-activated kinase inhibitor, PF-3758309, in colon cancer models - Pitts, Todd M.; Kulikowski, Gillian N.; Tan, Aik-Choon; Murray, Brion W.; Arcaroli, John J.; Tentler, John J.; Spreafico, Anna; Selby, Heather M.; Kachaeva, Maria I.; McPhillips, Kelly L.; Britt, Blair C.; Bradshaw-Pierce, Erica L.; et al. (Frontiers in Pharmacology, 2013)
The p21-activated kinase (PAK) family of serine/threonine kinases, which are overexpressed in several cancer types, are critical mediators of cell survival, motility, mitosis, transcription, and translation. In the study presented here we utilized a panel of CRC cell lines to identify potential biomarkers of sensitivity or resistance that may be used to individualize therapy to the PAK inhibitor PF-03758309. We observed a wide range of proliferative responses in the CRC cell lines exposed to PF-03758309, this response was recapitulated in other phenotypic assays such as anchorage-independent growth, three dimensional tumor spheroid formation, and migration. Interestingly, we observed that cells most sensitive to PF-03758309 exhibited up regulation of genes associated with a mesenchymal phenotype (CALD1, VIM, ZEB1) and cells more resistant had an up regulation of genes associated with an epithelial phenotype (CLDN2, CDH1, CLDN3, CDH17) allowing us to derive an epithelial-to-mesenchymal transition (EMT) gene signature for this agent. We assessed the functional role of EMT-associated genes in mediating responsiveness to PF-3758309, by targeting known genes and transcriptional regulators of EMT. We observed that suppression of genes associated with the mesenchymal phenotype conferred resistance to PF-3758309, in vitro and in vivo. These results indicate that PAK inhibition is associated with a unique response phenotype in CRC and that further studies should be conducted to facilitate both patient selection and rational combination strategies with these agents.